2017
DOI: 10.17221/614/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sowing and harvest dates on production of two different cultivars of sugar beet

Abstract: Small-plot trials conducted in 2013–2015 studied the impact of longer vegetation periods (by means of earlier drilling and/or later harvest) on production results of two sugar beet cultivars – one nematode-tolerant cultivar and one cultivar without such tolerance. The trials took place at two sites with different Heterodera schachtii infestation levels. In all trial seasons, root yield was significantly higher in the earlier drilled plots. On average, prolongation of the vegetation period in spring by 13 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…(sucrose%), SR% (sugar recovery%) and QZ (quality index%) were obtained in sugar beet roots harvested later at age of 210 days, which also contained lower values of Na%, K%, LS% (loss of sugar to molasses%) and AC (alkalinity coefficient), as compared with beets harvested earlier after 180 days from sowing, in the first and second season. These results are in agreement with those obtained by Cakmakci (2002); Aly (2006); Hussein, et al (2012); Awad, et al (2014) and Klara, et al (2017).…”
Section: Effect Of Harvest Age On Quality Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…(sucrose%), SR% (sugar recovery%) and QZ (quality index%) were obtained in sugar beet roots harvested later at age of 210 days, which also contained lower values of Na%, K%, LS% (loss of sugar to molasses%) and AC (alkalinity coefficient), as compared with beets harvested earlier after 180 days from sowing, in the first and second season. These results are in agreement with those obtained by Cakmakci (2002); Aly (2006); Hussein, et al (2012); Awad, et al (2014) and Klara, et al (2017).…”
Section: Effect Of Harvest Age On Quality Parameterssupporting
confidence: 93%
“…*Annual report of sugar crops council, Jan 2016 Mahmoud, et al (2008), Yousef and Abdel-Mottaleb (2009) and Enan, et al (2011) reported that the highest sucrose%, juice quality, as well as root and sugar yields/fed were obtained by increasing plant age at harvest from 180 up to 210 days after sowing. Klara, et al (2017) indicated that in all trial seasons, root yield was significantly higher in the earlier drilled plots. On average, prolongation of the vegetation period in spring by 13 days increased root yield by 10.9%.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This might be happened due to increase in temperature and respiration in delay harvest. Similar trend was reported elsewhere (Hemayati et al, 2012;Pavlů et al, 2017 andPaul et al, 2018a). 3).…”
Section: Brix (%) In Juicesupporting
confidence: 92%
“…Under dry environmental conditions, the proper sowing date of sugar beet plays a vital role in growth, production, physiological, and quality traits. It has been reported that the early sowing of sugar beet causes a marked increase in gross sugar content, and the highest yields of roots and sugars [11][12][13]. The key environmental variables that define the start of beet growing are temperature, soil moisture, and slight rate of rainfall [14].…”
Section: Introductionmentioning
confidence: 99%